Comparative study between Ketamine and Propofol versus Ketamine and Dexmedetomidine for Monitored Anaesthesia Care for Dilatation and Curettage surgeries in Daycare procedures - Sahoo, Ayaskant; Ruttala, Nagasatyasuryanarayana; Prasad, Rajendra; Behera, Swikruti; Banavathu, Eliya Naik (Journal of Medical Science, 2024)
Introduction. Anaesthesia is frequently administered through Monitored Anaesthesia Care (MAC) utilising various combinations of anaesthetic drugs for moderately painful operations like Dilatation and Curettage (D&C), which is preferably done as a daycare procedure. The hunt for improved drug combinations is always ongoing, and the pharmacological properties of the individual drugs are considered. In this regard, anaesthesiologists all over the world are quite fond of the combination of Ketamine and Propofol, which is also known as Ketofol. Recently, especially in situations involving MRI sedation, the combination of ketamine and dexmedetomidine (Dexket) has gained popularity. This study compares the combinations for MAC during D&C surgeries in a daycare setting.Aim. The primary objective was to estimate the recovery times using either combination. Secondarily, we would also compare the duration of analgesia, the haemodynamics, and the side-effect profiles of the two combinations.Material and Methods. This study enrolled 60 patients posted for elective D&C. According to standard institutional protocols, they were administered Ketofol(KP group) or Dexket(KD group), depending on the anaesthesia provider’s choice. The Ketofol group received Ketamine 1mg/kg and Propofol 1mg/kg with boluses of Ketamine 0.25mg/kg to maintain the depth of anaesthesia using Ramsay sedation score(RSS) >3. KD group received Dexmedetomidine intravenously 1mic/kg over 10 minutes followed by ketamine 1mg/kg boluses of Ketamine 0.25mg/kg to maintain the adequate anaesthetic depth of RSS>3.Results. The Recovery time in post-operative period was significantly prolonged in the KD group (mean 22.77 minutes) compared to the KP group (mean 17.8 minutes). The total duration of analgesia was also longer in the KD group (250 minutes vs 220 minutes in the KP group). It was seen that the hemodynamic variables (HR, SBP, DBP) were consistently higher in the KD group compared to the KP group. There was a significant difference in SBP, DBP, and MAP in the intraoperative period between the KP and KD groups till 4hr in the postoperative period.Conclusions. We conclude that a combination of Dexmedetomidine and Ketamine has longer recovery times and analgesia duration than a combination of Propofol and Ketamine. Side effects like postoperative nausea and vomiting are not significant. However, since the recovery times are comparatively longer in a daycare setting, dexmedetomidine and Ketamine may not be the preferred agents compared to the combination of Ketamine and Propofol in the context of a daycare setting.